Climate change, culture, and economics anthropological investigations - Wood, Donald C. (Bingley, U.K. : Emerald, 2015)
It is becoming increasingly difficult to deny that human activity is a factor in global climate change. This special volume of REA facilitates readers to better understand the ways in which people around the world have adapted (or failed to adapt) culturally to changing economic conditions caused by climate change. It focuses on specific situations in particular locations, showcasing (and confirming) the strength and value of intensive ethnographic or archaeological A<U+0302>?investigation. The authors discuss: 1) How has climate change affected production, distribution, or consumption at the local level? 2) Are environmental conservation and economic development mutually exclusive? 3) What roles can public and private institutions play in successful adaptation? 4) What kinds of parallels can be drawn between current social situations and those in the past with regards to climate change?
Institutional climate change adaptation efforts among the Sherpas of the Mount Everest region, Nepal / Pasang Sherpa -- Installing rooftop solar panels in private homes : the case of small electricity producers on Reunion Island (Indian Ocean) / Sophie Bouly de Lesdain -- <U+201c>Bug Wood<U+201d> : climate change, mountain pine beetles and risk in the Southeastern British Columbia logging industry / Patrick B. Patterson -- Conservation units, environmental services and frontier peasants in the central Amazon : multi-functionality, juxtaposition or conflict? / Ana Maria de Souza Bicalho, Scott William Hoefle -- Global warming or cash economy? Discourses of climate change and food in Eastern Highlands province, Papua New Guinea / Olivia Barnett-Naghshineh -- Farmers rainfall anticipation: incidence and patterns in Western Nigeria. Advantages of focus and problems of extrapolation in case studies / Jane I. Guyer -- Climate change policies and adaptive behaviour of farmers in Southern China / Meine Pieter van Dijk, Hao Li -- Is environmental uncertainty redefining fishing strategies? The use of the traditional lunar calendar to allocate fishing effort in Ende, Eastern Indonesia / Victoria C. Ramenzoni -- The origins of the sustainability concept : risk perception and resource management in early urban centers / Monica L. Smith -- Merchant resiliency and climate hazard vulnerability in the urban Philippines : anthropological perspectives on 2011s typhoons Nesat and Nalgae / Ty Matejowsky -- Environmental destruction, Guarani<U+0301> refugees and indigenous identity in urban Paraguay / Richard Reed.
Print version record
Keywords: Social Science -- Anthropology -- Cultural; Environmental economics; Climatic changes -- Research; Climatic changes -- History